Responses of various carbon to nitrogen ratios to microbial communities, kinetics, and nitrogen metabolic pathways in aerobic granular sludge reactor. (January 2023) - Zou, Xin; Gao, Mengjiao; Mohammed, Abdul; Liu, Yang
Graphical abstract: Highlights: Elevated ammonia concentration stimulated the growth of AAOB. FA inhibition might play a key role for autotrophic nitrification development. 2.7-fold higher ammonia oxidation rate was achieved from AAOB compared to HAOB. Limited ammonia oxidation capacities were observed in HAOB. Heterotrophic nitrification was the dominant pathway at high C/N ratios (12 and 6). Abstract: The role of different ammonia concentrations (mg N/L) (of 100 (carbon to nitrogen ratio (C/N) = 12; Stage I), 200 (C/N = 6; Stage II), 400 (C/N = 3; Stage III) and 200 (C/N = 6; Stage IV)) in nitrogen metabolic pathways, microbial community, and specific microbial activity were investigated in an aerobic granular sludge reactor. Heterotrophic ammonia oxidizing bacteria (HAOB) showed higher ammonia oxidation rates (AORs) than autotrophic ammonia oxidizing bacteria (AAOB) at higher C/N conditions (Stages I and II). Paracoccus was the dominant HAOB. AAOB, with only 0.2–0.3 % in relative abundance, showed 2.7-fold higher AORs than HAOB at elevated ammonia and free ammonia (FA) concentrations with C/N at 3. Nitrosomonas and a genus in Nitrosomondaceae family were the major AAOB. This study proposed that FA inhibition on heterotrophic bacteria might be the mechanism that contributes to the development of the autotrophic ammonia oxidation pathway and enrichment of AAOB.